The morphology and prevalence of the deltoid complex ligament of the ankle - Yammine, Kaissar (2017)
The deltoid ligament is a complex structure of the tibiotalar joint that limits the translation and tilting of the talus. It is often associated with injuries of the ankle joint. The deltoid complex ligament has 2 layers; one superficial with 4 bands and the other deep with 2 bands. Nevertheless, the prevalence and size of its components are reported with some variability in the literature. The aim of this meta-analysis is to generate weighted values of the prevalence, size, and attachment surface areas of its components. Eight studies met the inclusion criteria with a total of 142 ankle specimens. The analyses demonstrate that the most consistent component is the deep posterior tibiotalar (100%), followed by the tibiospring (≈94%), the tibionavicular (≈90%), and the tibiocalcaneal (85%). The superficial posterior ligament and the deep anterior tibiotalar ligament were the least prevalent (≈80% and ≈63%, respectively). The longest ligament was found to be the tibionavicular ligament and the shortest band was the deep posterior tibiotalar ligament. The tibionavicular ligament was the thinnest of all deltoid complex ligament components. This study yielded more accurate data on the frequency and size of its components. The possible absence of a component, particularly of the superficial layer, might compromise joint stability in acute ankle injuries.